Histochemical characterization, distribution and morphometric analysis of NADPH diaphorase neurons in the spinal cord of the agouti - Marco Aurelio M Freire; Marco Aurelio M Freire; Suzane C Tourinho; Joanilson S Guimarães; Joanilson S Guimarães; Jorge Luiz F Oliveira; Cristovam W Picanço-diniz; Walace Gomes-Leal; Antonio Pereira; Antonio Pereira (Frontiers Media S.A., 2008)
We evaluated the neuropil distribution of the enzymes NADPH diaphorase (NADPH-d) and cytochrome oxidase (CO) in the spinal cord of the agouti, a medium-sized diurnal rodent, together with the distribution pattern and morphometrical characteristics of NADPH-d reactive neurons across different spinal segments. Neuropil labeling pattern was remarkably similar for both enzymes in coronal sections: reactivity was higher in regions involved with pain processing. We found two distinct types of NADPH-d reactive neurons in the agouti’s spinal cord: type I neurons had large, heavily stained cell bodies while type II neurons displayed relatively small and poorly stained somata. We concentrated our analysis on type I neurons. These were found mainly in the dorsal horn and around the central canal of every spinal segment, with a few scattered neurons located in the ventral horn of both cervical and lumbar regions. Overall, type I neurons were more numerous in the cervical region. Type I neurons were also found in the white matter, particularly in the ventral funiculum. Morphometrical analysis revealed that type I neurons located in the cervical region have dendritic trees that are more complex than those located in both lumbar and thoracic regions. In addition, NADPH-d cells located in the ventral horn had a larger cell body, especially in lumbar segments. The resulting pattern of cell body and neuropil distribution is in accordance with proposed schemes of segregation of function in the mammalian spinal cord.